An evaluation of critical approaches to the customs union betwenn turkey and the European union - Kavak, Pınar Yörük (My University, 2005)
1963 Ankara Anlasması ile kararlastırılan, 1973 Katma Protokol’le ayrıntıları belirlenen ve 1 Ocak 1996 itibariyle Türkiye ile Avrupa Birligi arasında tam olarak uygulamaya giren Gümrük Birligi, Türkiye ekonomisine sekil veren önemli bir faktördür. Bu nedenledir ki özellikle Türk kamuoyunda yogun olarak tartısılmaktadır. Çalısmanın temel amacı bu elestirilerin dayandırıldıkları temellere göre kategorizasyonu ve degerlendirilmesidir. Sonuç olarak, Gümrük Birligi’ne yöneltilen elestirilerin ekonomik entegrasyona degil, ekonomik entegrasyonun modeli üzerine yogunlastıgı söylenebilir. Baska bir deyisle, AB ile Türkiye arasında gerçeklesecek bir ekonomik birlik, Türkiye ekonomisi için serbest ticaretten sonra en iyi seçenek olarak kabul görmektedir denebilir. Elestiriler dört ana kategoride toplanmıstır. _lk kategoriyi Gümrük Birligi’nin dayandıgı temel üzerine yapılan elestiriler olustururken, ikinci kategoriyi Gümrük Birligi’nin amacı üzerine yapılan elestiriler olusturur. Üçüncü ve dördüncü kategoriler ise sırasıyla Gümrük Birligi’nin Türkiye ekonomisi üzerine etkileri ile Gümrük Birligi’nin isleyisinden kaynaklı aksaklıklar olusmaktadır.

The Customs Union was determined by 1963 Ankara Agreement, detailed by 1973 Additional Protocol and became effective in 1996 between Turkey an the EC. Since it is one of major factors which effect Turkish economy, it has been very criticized in Turkey. The aim of the study is to make a categorization and evaluation of these critics. Although, there have been many arguments about this issue in Turkey, most of them have not criticize the direction. The critics are not generally concentrated on the concept of economic integration itself, but of its modelling. In other words, it can be said that there is a general consensus that Turkey’s economic integration with the EU is the most rational option. There are four basic categories regarding the essence of critics about the current CU in Turkey. The first one is critics on the source of the CU between Turkey and the EU. The second category is constituted by the critics on the aim of the CU. The third category of the critics on the CU are classified according to possible effects of the CU on an economy. The fourth category of the critics on the CU is about the functioning of it.
Keywords: Avrupa Birliği_Çok Taraflı Anlaşmalar ve Gümrük Birlikleri